Business Cycles, Unemployment and Entrepreneurial Entry: Evidence from Germany - Michael Fritsch; Alexander S. Kritikos; Katharina Pijnenburg (Institute for the Study of Labor (IZA), 2013)
We investigate whether people are more willing to become self-employed during boom periods or during recessions and to what extent business cycles or unemployment levels influence entries into entrepreneurship. Our analysis for Germany reveals that there is a positive relationship between unemployment rates and start-up activities. Moreover, new business formation is higher during recessions than in boom periods. This implies that new business formation is counter-cyclical. When disentangling periods of low and high unemployment we find that the effect of unemployment on new business formation is only statistically significant if the level of unemployment is below the trend, indicating a low unemployment retain effect.
Keywords: L26; E32; 330; self-employment; business cycle; unemployment; start-up